EFEKTIVITAS PENGGUNAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DALAM PROGRAM PENGENTASAN KEMISKINAN DI KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2010-2012 - Yayat Darinsyah; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research present describe the efecitivity use of income and outcome budgeting of Bengkalis Regency in 2011. Bengkalis Regency are one of Regency that have a highest income and outcome budgeting in Riau Province. Income of bengkalis still 2007-2011 has increase from Rp.112.355.796.050 be a Rp. 214.155.303.000. Composition income Bengkalis Regency still 6 years ago dominated from income transfer from central government Rp. 1.681.885.529.187 in 2007 and increase in 2012 be Rp. 3.210.456.010.424The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Bengkalis Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of Regencu Bengkalis, Chief of Social Bengkalis Regency, and House of Representatives Bengkalis Regency.The conclution of this research are income and outcome budgeting of Bengkalis Regency in 2011 to poverty programme have done in some unit society, likes: educations, healths, social protects, public facility. And effectivity of use income and outcome budgeting of Bengkalis Regency untill now not effectively. Its cause income and outcome budgeting of Bengkalis Regency untill 2013 most of used to outcome government and capital outcome.Keywords: effectivity, budget, income and poverty.